Trichotillomania Induced by Stimulant Therapy for ADHD: A Rare Case Report - Joshi, Pranav; Pokharel, Shreya; Upreti, Dikshya; Dhakal, Aashish (Annapurna Journal of Health Sciences, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder in the pediatric population, affecting approximately 5% of children globally. While stimulant medications such as methylphenidate and amphetamine are considered first-line treatments due to their efficacy, they are associated with a range of adverse effects, including appetite suppression, insomnia, and, more rarely, trichotillomania—a body-focused repetitive behavior characterized by compulsive hair pulling. Trichotillomania, although uncommon, can cause significant distress and impairment in daily functioning, particularly in young children. The association between stimulant use and trichotillomania has been reported in a few other articles across the world, which usually resolves after discontinuation of the stimulant medication. However, further documentation is required due to the limited number of cases and publications limited to only case reports. To support this clinical finding, we report a case of a 9-year-old female who presented with features of trichotillomania following treatment with Dextroamphetamine- amphetamine for ADHD.